Unit eight - Inland fisheries and aquaculture. [Training/Course material]. - Nguyen-Khoa, Sophie; Beveridge, Malcolm C.M.; Atapattu, Sithara S.; Smith, L. (2009)
This unit provides an introduction to the key characteristics of fisheries and aquaculture and the distinctions between them. It looks at their significance in farming systems and the water requirements involved. It proceeds to discuss the methods and tools available to assess water requirements for fisheries and aquaculture. The final sections of the unit look at the trade-offs for water allocation for fisheries and aquaculture and introduce perspectives on water governance and associated implications for water policies related to fisheries and aquaculture. Unit aims: To define and explain the nature of fisheries and aquaculture and the differences between them in relation to water resource management; To highlight the importance of fisheries and aquaculture to livelihoods; To explain the basis for assessment of fisheries and aquaculture water requirements in terms of quantity and quality; To present existing methods for assessing water needs in fisheries and aquaculture; To present existing methods for assessing water needs in fisheries and aquaculture; To introduce water resource management options for fisheries and aquaculture and related governance and policy implications.